PERIMBANGAN KEUANGAN ANTARA PEMERINTAH PUSAT DENGAN PEMERINTAH DAERAH DALAM PENGELOLAAN KEUANGAN DAERAH - Edward Hutagalung (Jurnal Ilmu Pemerintahan Widya Praja, 2016)
The ﬁ nancial relationship between central and local government can be deﬁ ned as a system that regulates how some funds were divided among various levels of government as well as how to ﬁ ndsources of local empowerment to support the activities of the public sector.Fiscal decentralization is the delegation of authority granted by the central government to theregions to make policy in the area of   ﬁ nancial management.One of the main pillars of regional autonomy is a regional authority to independently manage theﬁ nancial area. State of Indonesia as a unitary state of Indonesia adheres to a combination of elementsof recognition for local authorities to independently manage ﬁ nances combined with the element oftransferring ﬁ scal authority and supervision of the ﬁ scal policy area.General Allocation Fund an area allocated on the basis of the ﬁ scal gap and basic allocation whilethe ﬁ scal gap is reduced by the ﬁ scal needs of local ﬁ scal capacity. Fiscal capacity of local sources offunding that comes from the area of   regional revenue and Tax Sharing Funds outside the ReforestationFund.The results showed that the strengthening of local ﬁ scal capacity is in line with regional autonomy.